Maya 8 at a glance - Maestri, George (Wiley Pub., 2006)
One look and you'll see that this Maya book is different from all the others. It presents the core Maya features visually, using pages packed with striking graphics and loaded with concise explanations of the Maya interface. This expanded edition includes more tutorials; updated material on modeling, animation, rendering and dynamics; and new coverage of Toon Shaders, along with other exciting Maya tools. Engaging step-by-step lessons provide hands-on reinforcement as you learn. Start your adventures in Maya with this full-colour, visual guide—the perfect introduction to Maya 8.